Penanggulangan Anemia pada Remaja di Desa Sumbersekar Malang dalam Mendukung Sustainable Development Goals 3 - Bita Parga Zen; Hendry Setiawan; Devilke Yandriyani; Muhammad Nurwegiono (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
Adolescent female anemia is a health issue that increases the risk of chronic malnutrition and stunting in children. In Sumbersekar Village, Malang Regency, adolescent girls face limited awareness of the importance of hemoglobin, making prevention efforts challenging. This study aims to improve knowledge, promote early detection, and provide practical anemia prevention strategies. The methods used include interactive education on anemia symptoms and prevention, hemoglobin (Hb) testing to identify at-risk participants, distribution of iron supplement tablets, and demonstration of an app-based anemia monitoring system. Data were collected through Hb testing, participant observations, and satisfaction surveys. The results showed active participation of 160 adolescent girls, an increased in knowledge and awareness about anemia, smooth distribution of iron tablets, and better understanding of health monitoring through the application. Evaluation revealed that 95% of participants were highly satisfied with the program. In conclusion, the initiative effectively enhanced awareness, promoted early detection, and prevented anemia among adolescent girls in Sumbersekar Village